2002
DOI: 10.1093/treephys/22.8.507
|View full text |Cite
|
Sign up to set email alerts
|

Age- and size-related trends in woody plant shoot development: regulatory pathways and evidence for genetic control

Abstract: Woody plants exhibit significant and predictable patterns of change in morphology and physiology as they become older and larger. Four models of potential pathways controlling these changes are presented: a stimulus-response model in which fully developed organs respond to changes in environment (defined here as everything external to the organ); an extrinsic model in which the attributes of developing organs are determined by environmental factors; an intrinsic model in which changes are a result of programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
92
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 46 publications
4
92
0
1
Order By: Relevance
“…Experiments in a number of woody species (Doorenbos, 1954;Frank and Renner, 1956;Greenwood et al, 2010;McDaniel, 1980;Schwabe and AlDoori, 1973) suggest that the root system is a source of a juvenilizing factor, whereas defoliation experiments implicate leaves as the source of an adult-promoting factor (Ashby, 1948;Njoku, 1956b). Other studies have suggested that the overall size (Day et al, 2002;Greenwood et al, 2010) and growth rate (Borchert, 1964) of the shoot are key factors in this process. However, the different growth habits of the species used in these studies, as well as the fact that different traits were used as evidence of vegetative phase change in the different species, make it difficult to compare the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in a number of woody species (Doorenbos, 1954;Frank and Renner, 1956;Greenwood et al, 2010;McDaniel, 1980;Schwabe and AlDoori, 1973) suggest that the root system is a source of a juvenilizing factor, whereas defoliation experiments implicate leaves as the source of an adult-promoting factor (Ashby, 1948;Njoku, 1956b). Other studies have suggested that the overall size (Day et al, 2002;Greenwood et al, 2010) and growth rate (Borchert, 1964) of the shoot are key factors in this process. However, the different growth habits of the species used in these studies, as well as the fact that different traits were used as evidence of vegetative phase change in the different species, make it difficult to compare the results of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Gas exchange characteristics may change as trees become larger due to sizedependent variation in environmental and structural factors and their interactions, such as changes in light availability, hydraulic conductance, and carbon allocation (e.g., Yoder et al 1994;Gower et al 1996;Ryan and Yoder 1997). Some traits, such as leaf mass per area and sexual maturation, vary with meristem age independently of size (Bond 2000;Bond et al 2007;Greenwood et al 2008;Thomas 2011); however, developmental changes in gas exchange are driven by tree size rather than age (Day et al 2002;Mencuccini et al 2005;Bond et al 2007;Steppe et al 2011). Thus, we use the term size rather than age throughout this paper (McDowell et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…With the increased size of the tree, water and nutrients must be transported over increasing distances between the root and the apex [7]. The water supply to the leaves of the apex becomes constrained by gravity and hydraulic conductance.…”
Section: Discussionmentioning
confidence: 99%